Systematic meta-review: diagnostic accuracy of colon capsule endoscopy for colonic neoplasia with umbrella meta-analysis. - Ian Io Lei; Pablo Cortegoso Valdivia; Wojciech Marlicz; Karolina Skonieczna-Żydecka; Ramesh Arasaradnam; Rami Eliakim; Anastasios Koulaouzidis (Clinical Medicine)
Background: Despite the rising global incidence of colorectal cancer (CRC) and increasing pressure on endoscopy services, colon capsule endoscopy (CCE) has seen limited clinical uptake, primarily because of a lack of trust in its diagnostic accuracy. Although multiple systematic reviews and meta-analyses have reported reasonable polyp detection rates, scepticism persists. This meta-review and umbrella meta-analysis aimed to synthesise evidence on CCE’s diagnostic accuracy in polyp and CRC detection, using computed tomography (CT) colonography or colonoscopy as the reference standard. Methods: We conducted a systematic search of EMBASE, MEDLINE and PubMed for systematic reviews, with or without meta-analyses, evaluating the diagnostic accuracy of CCE in detecting polyps and CRC. A qualitative thematic review and synthesis were conducted following PRISMA guidelines. A bivariate generalised linear mixed model (GLMM) with random effects was used for pooled diagnostic accuracy estimates, and meta-regression was performed using restricted maximum likelihood (REML) estimation. Results: Nine systematic reviews (eight with meta-analyses) were included,1–9 comprising 3,472 participants in 28 unique primary studies after removing duplicates. The pooled per-patient diagnostic accuracy for detecting polyps of any size was: sensitivity: 0.79 (95% confidence interval (CI): 0.69–0.86); specificity: 0.77 (95% CI: 0.71–0.82) and area under the curve (AUC): 0.81 (95% CI: 0.47–0.96). For polyps ≥6 mm, the sensitivity, specificity and AUC were 0.80, 0.87 and 0.81, respectively. Detection of polyps ≥10 mm showed a sensitivity of 0.88, specificity of 0.95, and AUC of 0.95.Second-generation CCE (CCE2) demonstrated improved accuracy in any-size polyps: sensitivity: 0.90 (95% CI: 0.79–0.96), specificity: 0.81 (95% CI: 0.70–0.89) and AUC: 0.82 (95% CI: 0.46–0.96). For polyps ≥6 mm, CCE2 achieved AUC 0.92, and for polyps ≥10 mm, AUC 0.94. CCE2 subgroup analysis demonstrated high sensitivity for any polyp size (0.90) and polyps ≥6 mm (0.87), both with low heterogeneity (p>0.05, I² <25%). The pooled CRC detection sensitivity was 0.96 (95% CI: 0.73–1.00) after excluding missed cancers resulting from capsule battery exhaustion before excretion. Conclusion: CCE2 has high diagnostic accuracy for polyp and CRC detection. While technical challenges persist, CCE2 shows promise as a complementary diagnostic tool to help address increasing endoscopy service demands.